The Borehole Water Intakes Mathematical Models with a Branched and Circular Connection Schemes for Prefabricated Water Conduits - V. V. Veremenyuk; V. V. Ivashechkin; V. I. Krytskaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2020)
Borehole water intakes of underground water are widely used for water supply of agricultural towns, urban settlements, small and large cities and megacities. The number of consumers in these localities determines the number of water intakes, the number of wells, their productivity, location and connection to the prefabricated water conduits. Due to the increase in the use of underground water, the existing water intakes are being reconstructed and expanded. These works are accompanied by grouting of failed wells, their re-drilling, drilling of additional wells, re-laying of old and laying of new prefabricated water conduits. All this causes the complexity of the configuration of prefabricated water conduits due to the construction of jumpers and rings, the emergence of new wells with connection lines. Under the new conditions, in order to properly develop water intake operating modes which meet the minimum energy consumption for lifting and delivering a required volume of water to the collection-and-control tanks, to accurately choose the appropriate water lifting equipment in wells, to develop measures for intensifying water intake alongside with a forecast of their efficiency and to optimize the operation of the water intake, it is necessary to create its mathematical model that allows performing complex calculations. Water intakes with ramified prefabricated water conduits, as well as with an area scheme of the location of wells and a ring scheme of the connection of prefabricated water conduits are the most difficult object for mathematical modeling. The methods of calculating such water intakes are not sufficiently reflected in the literature, and there are no specific examples of calculation. The present article aims to clarify the methodology for calculating borehole water intakes with ramified prefabricated water conduits and with a ring scheme of their connection.